Strategies for Enhancing Students' Mathematical Reasoning and Disposition Ability in a Freedom Curriculum - Getut Pramesti; Enny Pardjijanti; Arofah Adzarori Nugraha (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
It is crucial to have suitable learning models in the Freedom curriculum, allowing students sufficient time to delve into concepts and improve skills, particularly in mathematical reasoning and disposition. CORE learning (Connecting, Organizing, Reflecting, and Extending) is a different approach to enhancing upper school students' mathematical reasoning and disposition abilities. This quantitative study employs descriptive and two-way multivariate analysis to examine the impact of learning models and gender on students' mathematical reasoning and disposition abilities. The study focuses on grade IX students at a public senior high school in Surakarta, Indonesia. The control group is class Phase E-8, which follows a direct learning approach and is known as the Non-CORE class. In the meantime, the Phase E-10 class is an experimental class implementing the CORE learning model. The study findings show variances in mathematical thinking and attitude among high school students in CORE versus non-CORE classes. Additionally, there is no reliance on enforcing CORE learning on male and female students, suggesting that CORE learning can be suggested for enhancing mathematical reasoning skills and disposition ability of all students irrespective of gender. CORE learning has been proven to be an effective strategy for improving students' mathematical reasoning and disposition through education oriented towards a constructivist approach centered on students, where students actively construct their knowledge through a series of processes that connect, organize, reflect, and extend concepts. This study contributes to the discourse on constructivist pedagogy by providing strong evidence that the CORE learning model improves mathematical reasoning and attitudes among upper secondary students. Those taught with CORE outperform peers in traditional settings in both cognitive and attitudinal measures. The lack of gender-based differences indicates CORE supports equitable learning. Aligned with Indonesia’s Freedom Curriculum, the model promotes active, student-centered learning and shows promise as a scalable, inclusive approach to improving math proficiency and engagement.